Daratumumab Prevents Experimental Xenogeneic Graft-Versus-Host Disease by Skewing Proportions of T Cell Functional Subsets and Inhibiting T Cell Activation and Migration - Gao, Yang; Shan, Wei; Gu, Tianning; Zhang, Jie; Wu, Yibo; Li, Xiaoqing; Zeng, Xiangjun; Zhou, Hongyu; Chen, Zhi; Xiao, Haowen (Frontiers in Immunology, 2021)
Graft-versus-host disease (GVHD) remains the major cause of mortality and morbidity in non-relapse patients after allogeneic hematopoietic cell transplantation (allo-HCT). As the number of patients undergoing allo-HCT increases, it will become imperative to determine safe and effective treatment options for patients with GVHD, especially those who become refractory to systemic steroid therapy. Daratumumab (Dara), a humanized IgG1 (ĸ subclass) monoclonal antibody targeting the CD38 epitope, is used for the treatment of multiple myeloma. CD38 is a multifunctional ectoenzyme that behaves either as an enzyme, a cell adhesion molecule or a cell surface receptor involved in cell signaling. CD38 is also expressed on various immune effector and suppressor cells. However, the role of CD38 in the immune response remains elusive. We questioned whether CD38 is a potential therapeutic target against alloreactive T cells in the GVHD pathological process. Here, we investigated the impact of Dara on xenogeneic GVHD (xeno-GVHD) and graft-versus-leukemia (GVL) effects in a humanized murine model of transplantation, where human peripheral blood mononuclear cells were adoptively transplanted into immunocompromised NOD.SCID.gc-null (NSG) mice. Mice receiving Dara treatment experienced less weight loss, longer survival and lower GVHD scores compared with those in the control group. Histological evaluations, flow cytometry, RNA-sequencing and RT-qPCR analysis revealed that Dara efficaciously mitigated GVHD through multiple mechanisms including inhibition of the proliferation, activation and differentiation of CD8+ cytotoxic T cells, reduced expression of cytotoxic effector molecules, pro-inflammatory cytokines, chemokines and chemoattractant receptors by T cells and promotion of immunosuppressive T cells. More importantly, Dara preserved the GVL effect in a humanized mouse model of leukemia by metabolic reprograming of T cells to promote the induction of Th17, Th1/17 and Tc1/17 cells. Our findings indicate that Dara may be an attractive therapeutic option to separate GVHD from GVL effects in patients with hematopoietic malignancies receiving allo-HCT.